Study on failure mechanism on rechargeable alkaline zinc–Air battery during charge/discharge cycles at different depths of discharge - Zhang, Donghao; Hu, Wenbin (Frontiers in Chemistry, 2023)
Zinc–air battery (ZAB) is a promising candidate for energy storage, but the short cycle life severely restricts the wider practical applications. Up to date, no consensus on the dominant factors affecting ZABs cycle life was reached to help understanding how to prolong the ZAB’s cycle life. Here, a series of replacement experiments based on the ZAB were conducted to confirm the pivotal factors that influence the cycle life at different depths of discharge (DOD). The morphology and composition of the components of the battery were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) and chemical titration analyses. SEM images and XRD results revealed that the failure of the zinc anode gradually deepens with the increase of DOD, while the performance degradation of the tricobalt tetroxide/Carbon Black (Co3O4/CB) air cathode depends on the operating time. The concentration of CO32– depends on the charge/discharge cycle time. The replacement experiments results show that the dominant factors affecting the ZAB’s cycle life is the reduction of active sites on the surface of Co3O4/CB air cathode at a shallow DOD, while that is the carbonation of the electrolyte at a deep DOD. The reduction of active sites on the surface of Co3O4/CB air cathode is caused by the coverage of K2CO3 precipitated by carbonation of the electrolyte, suggesting that the carbonation of the alkaline electrolyte limits ZAB’s cycle life. Therefore, this work not only further discloses the failure mechanism of ZAB, but also provides some feasible guidance to design a ZAB with a long cycle life.